2009
DOI: 10.2340/16501977-0393
|View full text |Cite
|
Sign up to set email alerts
|

Predicting walking ability following lower limb amputation: A systematic review of the literature

Abstract: The heterogeneity of methods and outcome measures used in the identified studies make comparison difficult and, in part, explains conflicting conclusions in relation to predictive factors. Further investigation of predictive factors is needed to estimate walking potential more accurately and guide targeting of modifiable factors to optimize outcome after lower limb amputation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

21
176
6
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(220 citation statements)
references
References 44 publications
21
176
6
9
Order By: Relevance
“…Indeed, bilateral amputations have been found to impede physical functioning to a greater extent than unilateral limb loss. 40,41 Shorter time elapsed since amputation was associated with steeper increases in general adjustment over time. Delays in rehabilitation admission may be indicative of more complex cases, which could account for the less pronounced increase in general adjustment observed.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, bilateral amputations have been found to impede physical functioning to a greater extent than unilateral limb loss. 40,41 Shorter time elapsed since amputation was associated with steeper increases in general adjustment over time. Delays in rehabilitation admission may be indicative of more complex cases, which could account for the less pronounced increase in general adjustment observed.…”
Section: Discussionmentioning
confidence: 99%
“…5 In contrast, postoperative functional ability does not seem to be related to prosthetic outcome. 14 Leung et al 28 found that the motor subscore of the functional independence measure (FIM) nor the FIM total score on admission was correlated to prosthetic use in their sample of 33 patients with lower limb amputation. However, in the present study, ambulation ability after amputation was an important factor determining prosthetic use.…”
Section: Discussionmentioning
confidence: 99%
“…4 In a systematic review on predictors of prosthetic use after lower limb amputation, Sansam et al concluded that the effect of comorbid conditions on walking with a prosthesis is not clear at all. 14 They found large differences between the used methodology and definitions of medical conditions in these studies. In all studies, single medical conditions were investigated in relation to prosthetic use, instead of multiple interacting diseases, often seen in geriatric patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a clear need to systematically address these points and evaluate prosthesis performance over and above the calculation of transition work and jointmechanics. The implications extend to general health themes as an increased embodiment of the prosthesis may lead to an improved own body image, a more active life style, and decreased social isolation [15].…”
mentioning
confidence: 99%